2005
DOI: 10.1002/ejic.200500097
|View full text |Cite
|
Sign up to set email alerts
|

The Fenton Reaction in Aerated Aqueous Solutions Revisited

Abstract: The oxidation of alcohols in aerated acidic aqueous solutions by the Fenton reagent is a chain reaction. The length of the chain depends linearly on the number of CHnOR (n = 1 or 2) groups in the alcohol. The reaction is accelerated by increasing the concentration of Fe(H2O)62+, but this cation is also active in at least one of the termination steps of the chain reaction. Addition of ethanol to a solution containing sucrose shortens the chain length. Saturation with dioxygen, instead of air, increases the chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…An investigation under more physiologically relevant conditions showed that the reaction between Fe II ðaqÞ and H 2 O 2 apparently occurs rapidly enough (within the range of 10 3 -10 4 M À1 s À1 at pH 7 and 37°C) to be capable of causing significant, and even lethal damage if DNA repair enzymes are knocked out and/or the steady-state level of H 2 O 2 is not controlled [21]. Whether this higher second-order rate constant represents reaction (2) only and excludes autocatalytic oxidation of Fe II ðaqÞ is unclear, however [25,26]. In any case, iron-sulfur cluster and DNA damage due to this ''in vivo superoxide-driven Fenton chemistry'' is believed to be the predominant contributor to intracellular oxidative stress in bacteria [27][28][29].…”
Section: Aqueousmentioning
confidence: 99%
“…An investigation under more physiologically relevant conditions showed that the reaction between Fe II ðaqÞ and H 2 O 2 apparently occurs rapidly enough (within the range of 10 3 -10 4 M À1 s À1 at pH 7 and 37°C) to be capable of causing significant, and even lethal damage if DNA repair enzymes are knocked out and/or the steady-state level of H 2 O 2 is not controlled [21]. Whether this higher second-order rate constant represents reaction (2) only and excludes autocatalytic oxidation of Fe II ðaqÞ is unclear, however [25,26]. In any case, iron-sulfur cluster and DNA damage due to this ''in vivo superoxide-driven Fenton chemistry'' is believed to be the predominant contributor to intracellular oxidative stress in bacteria [27][28][29].…”
Section: Aqueousmentioning
confidence: 99%
“…It is assumed that hydrogen peroxide reduces peptide-Cu(II) to peptide-Cu(I), this is followed by the reaction of Cu(I) with hydrogen peroxide to give Å OH [28]. However, it should be mentioned that the study clearly demonstrates that the mechanism of the Fenton reaction and Fenton-like reactions, in aerated solutions containing organic substrates, is considerable more complex than assumed earlier [29,30].…”
Section: Introductionmentioning
confidence: 98%
“…[7] That is, the second approximately 400-fold slower reactionh as, under the given experimental conditions, ah alf-life in the region of seconds. Assuming that the first ap-proximately 260 nmol mL À1 of CH 3 radicals produced are quenched by O 2 to yield to al arge extent the observedM eOH (see also MeOH quantification below), [54] the effective yield of CH 3 radicals in the reactions reported in Ta ble 1i sm uch larger (over 50 %). Assuming that the first ap-proximately 260 nmol mL À1 of CH 3 radicals produced are quenched by O 2 to yield to al arge extent the observedM eOH (see also MeOH quantification below), [54] the effective yield of CH 3 radicals in the reactions reported in Ta ble 1i sm uch larger (over 50 %).…”
Section: Introductionmentioning
confidence: 99%